The Utilization Of Coconut Tombong As A Raw Material For Flour - Siahaya, Griennasty Clawdya; Titaley, Samuel; Rehena, Zasendy (Agrikan: Jurnal Agribisnis Perikanan, 2021)
This study is the first step in developing coconut (Cocos nucifera) tombong which has not been utilized by society. The purpose of this study is to obtain a proper drying time in producing a nutrient-grade coconut tombong flour. This study used an experimental design with a complete randomized design where the coconut tombong was dried at 50°C for 6,7 and 8 hours. Furthermore in the analysis of content carbohydrate, protein, fat, ash content, crude fiber and water content. The results of the analysis showed that coconut tombong flour with 8 hours drying produced the best of coconut tombong flour compared with 6 and 7 hours drying, with lower moisture content 11, 7353%, fat 8,1666%, protein 11,7158%, ash content 7,4917% and crude fiber 11,8421%. The results of statistical test show that the drying treatment of 6, 7 and 8 hours gives a very significant difference to the average chemical properties (carbohydrate, moisture content, protein, fat, ash content, crude fiber) coconut tombong flour with Fvalue > Ftable 5% or significance value of all treatments is smaller than alpha value 0.05. Based on these results, it can be concluded that coconut tombong  flour which through the drying process at 50°C for 8 hours (L3) is the best treatment among two other treatments (L1 and L2) which has the potential to be further developed as various substitution materials food products.